Simulation of Ethyl Tert-Butyl Ether Production from Tert-Butyl Alcohol and Ethanol in Reactive Distillation - Suttichai Assabumrungrat; Varong Pavarajarn; Darin Wongwattanasate; Piyasan Praserthdam (ASEAN Journal of Chemical Engineering, 2005)
Reactive distillation was applied for the synthesis of ethyl tert-butyl ether (ETBE) from a liquid-phase reaction between tert-butyl alcohol (TBA) and ethanol (EtOH) catalyzed by commercial ~-zeolite catalyst with Si/AI ratio of 55. The major side reaction of this system was the dehydration of TBA to isobutene (lB). From the present researchers' previous work, it was found that B-zeolite was superior to commercial Amberlyst-15 catalyst in reaction selectivity. The kinetic parameters for the reactions, which were determined using a semibatch reactor operated at various temperatures, were used for simulation in Aspen Plus TN program. Various operating parameters, such as heat duty, molar ratio of Hz0: EtOH, and refluxratio, were investigatedfor their effectson reactive distillation performance. Keywords: ,B-zeolite,ethyl tert-butyl ether (ETBE) synthesis, and reactive distillation.